Comparison of Computer Algorithms and Visual Based Methods for Plant Layout - Scriabin, Michael; Vergin, Roger C. (Management Science, 1975)
Increasing emphasis on the reduction of materials handling costs in the modern plant has led to research into new methods of planning the process type layout in such a way as to minimize these costs. This project compares the performances of three highly rated computer algorithms prescribed for the solution of the plant layout problem with the performances of selected human subjects using the manual and visual methods still used and recommended by industrial engineers for plant layout design. The objective of this comparison is to determine whether there is in fact an advantage to using one of the available computer programs to solve the problem, instead of designing the layout by traditional visual-based methods. These tests, performed under the control of a computer system which accurately recorded the solutions achieved by each subject, show not only that the computer algorithms do not perform better than selected human subjects in the design of plant layouts, but that the human subjects, without the benefit of any prescriptive help from a computer, actually achieve layouts which are stochastically better than those produced by the computer programs.